Rapid age assessment in the Namib Sand Sea using a portable luminescence reader - Stone, AEC; Bateman, MD; Thomas, DSG (Elsevier, 2015)
A rapid assessment of burial age for sedimentary materials is useful to aid in-situ interpretation of sites and sequences during fieldwork. This can assist with targeted field sampling strategies for full dating back in the laboratory, for example when the study is concerned with reconstructing landscape dynamics during a specific time period. Field-based luminescence measurements are possible using a portable luminescence reader; the challenge is translating relative portable luminescence reader signal intensities of samples into an estimate of age. This study uses a portable luminescence reader for the first time in the analysis of African dunefield sediments. Samples from the Namib Sand Sea (NSS) with established luminescence ages are used to assess what in-situ information about relative sample age can be gleamed at and between sites using the portable luminescence reader, and to establish whether first-order estimates of sample age can be obtained. Two sites in the NSS, which are of modern, very late Holocene and last interglacial age were selected for this assessment and a simple calibration between portable luminescence reader signals and sample age is made. Results show that portable luminescence reader signals differ by over two orders of magnitude between late Holocene and last interglacial age samples and that useful relative-age information can be established using bulk material in the field. Predicted ages from portable luminescence reader signals using a linear regression appear to be indicative and useful. Further development of this calibration using a wider range of sample ages would confirm its applicability in the NSS, and a similar approach is applicable to other sand sea environments.